The Role of Extraordinary Chambers in the Courts of Cambodia in trying Khmer Rouge Human Rights Offender in Cambodia - Haq, Ahza Arzanul; Krisanti, Dea Putri; Wiguna, Zein Ibnu (Universitas Sebelas Maret, 2020)
Conflict often occurs when two or more interests are in contradiction and no one wants to concede. We know a variety of conflicts today, from the conflict preexisting since a long time ago such as intertribal conflict to more modern conflict such as a state’s tapping over another. The way of resolving conflict is also varying according to the types of conflict, big conflict such as interstate conflict or the one attracting the world’s attention, using more complex resolution and usually using the third party. Therefore, a special organization will be founded to solve a conflict. One of organizations created to solve a conflict is the Extraordinary Chambers in The Courts of Cambodia (ECCC) aiming to try the war criminals during Khmer Rouge humanity crime incidence in 1975-1979. Humanity crime occurring in Cambodia is one of largest humanity tragedies in modern era post 2nd World War. This ECCC was founded because at that time Cambodia’s National Justice Institution could not try the perpetrator of humanity crime. Cambodian government along with UN then agreed to found a justice institution specifically aiming to deal with and to resolve Khmer Rouge case.